The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.heliyon.2020.e04832
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Mhp462 antibody induced by natural infection but not in vitro culture of Mycoplasma hyopneumoniae

Abstract: Mycoplasma hyopneumoniae is the respiratory pathogen of porcine enzootic pneumonia, a chronic respiratory infectious disease that causes substantial pecuniary losses to pig husbandry worldwide. Commercial bacterins only provide incomplete protection and do not prevent the colonization and transmission of M. hyopneumoniae . Identification of new protective antigens is a key imperative for the development of more effective novel vaccine. The objective of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Based on the characteristics of the Mhp366 protein, we developed two ELISAs, one for screening serological immunodominant protein antigens [ 12 ] and another for further screening the discriminative immunodominant proteins that can distinguish between anti- M. hyopneumoniae IgG in inactivated bacterin-induced hyperimmune sera and convalescent sera resulting from natural M. hyopneumoniae infection [ 13 ]. The studies identified 15 serological immunodominant proteins and 1 discriminative serological immunodominant protein, Mhp462 [ 14 ]. These data suggest that a Mhp366-based ELISA has potential to be used as a diagnostic tool to detect natural M. hyopneumoniae infection.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the characteristics of the Mhp366 protein, we developed two ELISAs, one for screening serological immunodominant protein antigens [ 12 ] and another for further screening the discriminative immunodominant proteins that can distinguish between anti- M. hyopneumoniae IgG in inactivated bacterin-induced hyperimmune sera and convalescent sera resulting from natural M. hyopneumoniae infection [ 13 ]. The studies identified 15 serological immunodominant proteins and 1 discriminative serological immunodominant protein, Mhp462 [ 14 ]. These data suggest that a Mhp366-based ELISA has potential to be used as a diagnostic tool to detect natural M. hyopneumoniae infection.…”
Section: Introductionmentioning
confidence: 99%